Abnormal sodium and water homeostasis in mice with defective heparan sulfate polymerization - Olde Engberink, Rik H. G. (PLoS One, 2019)
Glycosaminoglycans in the skin interstitium and endothelial surface layer have been shown to be involved in local sodium accumulation without commensurate water retention. Dysfunction of heparan sulfate glycosaminoglycans may therefore disrupt sodium and water homeostasis. In this study, we investigated the effects of combined heterozygous loss of heparan sulfate polymerization genes (exostosin glycosyltransferase 1 and 2; Ext1(+/-)Ext2(+/-)) on sodium and water homeostasis. Sodium storage capacity was decreased in Ext1(+/-)Ext2(+/-) mice as reflected by a 77% reduction in endothelial surface layer thickness and a lower skin sodium-to-glycosaminoglycan ratio. Also, these mice were characterized by a higher heart rate, increased fluid intake, increased plasma osmolality and a decreased skin water and sodium content, suggesting volume depletion. Upon chronic high sodium intake, the initial volume depletion was restored but no blood pressure increase was observed. Acute hypertonic saline infusion resulted in a distinct blood pressure response: we observed a significant 15% decrease in control mice whereas blood pressure did not change in Ext1(+/-)Ext2(+/-) mice. This differential blood pressure response may be explained by the reduced capacity for sodium storage and/or the impaired vasodilation response, as measured by wire myography, which was observed in Ext1(+/-)Ext2(+/-) mice. Together, these data demonstrate that defective heparan sulfate glycosaminoglycan synthesis leads to abnormal sodium and water homeostasis and an abnormal response to sodium loading, most likely caused by inadequate capacity for local sodium storage.